Output feedback finite‐time stabilization of a class of nonlinear time‐delay systems in the p‐normal form. (23rd April 2020) - Wang, Xuhuan; Huang, Shipei; Xiang, Zhengrong
Summary: This article investigates the finite‐time output feedback stabilization problem for a class of nonlinear time‐varying delay systems in the p ‐normal form. First, a reduced‐order state observer is designed to estimate the unmeasurable state. Then, an output feedback controller is constructed, with the help of the finite‐time Lyapunov stability theorem, it is proved that the state of the resulting closed‐loop system converges to the origin in finite time. Two simulation examples are given to verify the effectiveness of the proposed scheme.